On monodromy map - Jharna D. Sengupta (International Journal of Mathematics and Mathematical Sciences)
Let Γ be a Fuchsian group acting on the upper half-plane U and having signature {p,n,0;v1,v2,…,vn}; 2p−2+∑j=1n(1−1vj)>0.